Update in Management of Foot and Ankle Disorders - Badekas, Thanos (IntechOpen, 2018)
With this book, you'll be able to update your knowledge in the field of foot and ankle surgery and pathology. This book includes a sport injuries section dedicated to Achilles tendon injuries in athletes and to ankle injuries in basketball players. The next section is about the management of pediatric and adult flatfoot deformity and the recent advances in this field. The third section is unique as it is about quality control in patients with foot and ankle injuries. I believe this section will be very helpful to foot and ankle practitioners to better asses the functionality and quality of life in their patients. The last section is on the third generation of percutaneous forefoot surgery and includes a novel system of Diabetes Ground Control. This book is a useful tool in your practice armamentarium.